2007
DOI: 10.1038/nchembio.2007.16
|View full text |Cite
|
Sign up to set email alerts
|

Splicing factor SF3b as a target of the antitumor natural product pladienolide

Abstract: Pladienolide is a naturally occurring antitumor macrolide that was discovered by using a cell-based reporter gene expression assay controlled by the human vascular endothelial growth factor promoter. Despite the unique mechanisms of action and prominent antitumor activities of pladienolides B and D in diverse in vitro and in vivo systems, their target protein has remained unclear. We used 3H-labeled, fluorescence-tagged and photoaffinity/biotin (PB)-tagged 'chemical probes' to identify a 140-kDa protein in spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
604
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 569 publications
(656 citation statements)
references
References 21 publications
24
604
0
5
Order By: Relevance
“…A sendai virus vector encoding FIR showed synergistic effects with cisplatin on malignant mesothelioma (28). Furthermore, SF3b is a cancer treatment target (14,29). Since the FIR/FIRDexon2/SAP155 complex is induced in colorectal cancers and disrupts proper FIR premRNA splicing, FIR splicing variants may be novel cancer screening markers (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…A sendai virus vector encoding FIR showed synergistic effects with cisplatin on malignant mesothelioma (28). Furthermore, SF3b is a cancer treatment target (14,29). Since the FIR/FIRDexon2/SAP155 complex is induced in colorectal cancers and disrupts proper FIR premRNA splicing, FIR splicing variants may be novel cancer screening markers (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…9,12 Therefore targeting the spliceosome may be a novel therapeutic approach for the treatment of CLL. Several compounds are available for this purpose, [13][14][15][16] including meayamycin B 17,18 and the structurally related spliceostatin A (SSA). 16 SSA is a synthetically modified analog of the natural product FR901464, 19 while meayamycin B is prepared by total synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…32,34,83 A mapping of these mutations on the pseudo-atomic model showed that they cluster around 2 regions in the SF3b structure (Fig. S25 and Video S7).…”
Section: Sf3b145 -A Stem Loop Binding Protein Containing An Rnase H-lmentioning
confidence: 99%
“…S27), analogous to its role in the U11/U12 di-snRNP. SSA is also known to bind to SF3b130 and SF3b155 34 and based on our SF3b pseudo-atomic model (Fig. 2B), we conjecture that these interactions might lock the SF3b130-SF3b155 interaction (Fig.…”
Section: Sf3b -A Fuzzy Complexmentioning
confidence: 99%
See 1 more Smart Citation